ApoB, small-dense LDL-C, Lp(a), LpPLA2 activity, and cognitive change. (28th May 2019) - Pokharel, Yashashwi; Mouhanna, Farah; Nambi, Vijay; Virani, Salim S.; Hoogeveen, Ron; Alonso, Alvaro; Heiss, Gerardo; Coresh, Josef; Mosley, Thomas; Gottesman, Rebecca F.; Ballantyne, Christie M.; Power, Melinda C.
Abstract : Objective: To examine the association of specific lipoproteins/inflammatory enzyme with cognitive change. Methods: We examined the association of apolipoprotein B (ApoB), small-dense low-density lipoprotein cholesterol (sdLDL-C), lipoprotein (a) (Lp[a]), and lipoprotein-associated phospholipase A2 (LpPLA2 ) activity with 15-year change in Delayed Word Recall Test, Digit Symbol Substitution Test (DSST), Word Fluency Test (WFT), and overall summary score in 9, 350 participants in the Atherosclerosis Risk in Communities study. We assessed interaction by race, sex, education, APOE ε4 status, and statin use. We also addressed questions of informative missingness, the role of stroke, and the influence of fasting status. Results: The mean (SD) age was 63.4 (5.7) years; 56.4% were women and 17.4% were black. We observed faster cognitive decline on DSST and global z scores with every 10-mg/dL higher sdLDL-C level (Δ DSST z score, −0.010; 95% confidence interval [CI] −0.017, −0.002 and Δ global z score, −0.011; −0.021, −0.001) and the highest vs the lowest ApoB quintiles (Δ DSST z score, −0.092; −0.0164, −0.019 and Δ global z score, −0.101; −0.200, −0.002). Association for the ApoB quintiles with Δ global z score (−0.10) was comparable with that of having 1 APOE ε4 allele (−0.11). Higher Lp(a) was associated with slower decline in DSST, WFT, and global z scores. LpPLA2 activity was not associated with cognitive change. Results were similar in sensitivity analyses. The associations of sdLDL-C or Lp(a) on cognitive change were more pronounced in statin users. Conclusions: Optimal control of atherogenic lipoproteins such as ApoB and sdLDL-C in midlife for cardiovascular health may also benefit late-life cognitive health.